Indonesia animation IP Industry Life Cycle barriers and expectations to grow national economic development - Sasongko, Hario (Technium Social Sciences Journal, 2022)
Creative industry is no doubt has great potential role in economic development and the animation industry is one of the creative industries that have attracted business concern with the increasing numbers of intellectual properties (IPs) for local content and have the potential for development as the identity of the Indonesian nation. The study aim to address the position of Indonesia animation industry in the phases of the industry life-cycle, analyze the barriers that hinder the development process using qualitative approach to forecast the future of the industry and discussing expectations that should be achieved.